DEPRESSION WITHIN UNDERGRADUATE STUDENTS (Journal of Pharmaceutical Negative Results, 2022)
Background: Present research study was conducted to identify prevalence of depression among undergraduate nursing students because it will help to prevention and promotion of their mental health that can result in good quality life in view physical, mental and social wellbeing.Objective: Research study was conducted with objective oassess depression among undergraduate nursing students.Methodology: Cross sectional research descriptive design and exploratory approach was used to depression with PHQ9 scale among 100 undergraduate nursing students of Krishna Institute of Nursing Sciences Karad which was selected by non-probability convenient sampling technique. Samples were selected according to inclusion and exclusion criteria. Formal ethical permission was received from Krishna Institute of Medical Sciences Deemed To Be University Karad. Before collecting the data formal inform and written consent was taken from students to conduct study on them. Data analysis was done with descriptive statistics and inferential statistics.Result: Result of present study reveals that 20% suffering with Minimal depression, 35% suffering with Mild depression, 10% suffering with Moderate depression, 17% suffering with moderately severe depression and 18% suffering with severe depression.Conclusion: Research reveals results that undergraduate aresufferings with Mild depression some planning of some intervention should be done and it should be implement to reduce depression and increase overall performance and health status.